Kajian Etnoliguistik Terhadap Istilah Penamaan Galungan - Sefira Amelia Rosadha; Sofi Ullanuha Cahyani; Taswirul Afkar (Politeknik Kampar, 2024)
Bali Province is located between the island of Java to the west and the island of Lombok to the east. The island of Bali is famous as a tourist destination and also various strong traditional events, one of which is the Galungan ceremony. The naming used for the Galungan ceremony is related to the language and culture of the Balinese people. This relationship can be proven by the terms used in naming the Galungan ceremony in Bali. This research formulates the problem of (1) What are the meanings and values contained in the Galungan celebration for the Balinese people, (2) What is the lexical and grammatical meaning of the term, (3) what is the function of this meaning. The aims of this research are (1) to describe the meaning and values contained in the Galungan celebration for the Balinese people, (2) to describe the lexical meaning and grammatical meaning of the term, and (3) to describe the function of this meaning. The analysis used is an ethnolinguistic analysis of the terms used in naming the Galungan ceremony in Bali. It is hoped that the results of this research will increase knowledge regarding the terms used in naming the Galungan ceremony in Bali, as well as become a reference for ethnolinguistic research with research objects in the same or different fields.